Atonement - God’s Plan for Reconciliation - Stephanie Lamour (Sekolah Tinggi Teologi Erikson-Tritt Manokwari, 2023)
The theme of atonement is developed through Scripture from its introductory framework in the sacrificial system to its completion in Christ and culmination in his kingdom. This paper approaches the theme of atonement through the framework of biblical theology to trace the development of this theme through four key passages - Leviticus 16:15-19, Psalm 40:6-8, Hebrews 10:1-14, and Revelation 5:9-14. A foundation for understanding atonement is set forth in the sacrificial system which presents atonement as a particular, sacrificial, priestly activity to bring about reconciliation for sin. Psalm 40 develops this idea by explicitly stating the need for obedience and setting forth a type of a kingly, obedient one. Hebrews 10 shows how both Leviticus 16 and Psalm 40 are pointing to Christ - the priest-king who is the perfect, effective, once-for-all sacrifice. Lastly, the allusion to the subjection of all to the reign of Christ (Heb. 10:12-13), points forward to Revelation 5 where reconciled people have access to the presence of the reigning Christ.Tema penebusan dikembangkan di seluruh Kitab Suci dari kerangka awalnya dalam sistem korban hingga penggenapannya di dalam Kristus dan puncaknya di kerajaan-Nya. Artikel ini mendekati tema penebusan melalui kerangka teologi biblika untuk menelusuri perkembangan tema ini dalam empat teks kunci - Imamat 16:15-19, Mazmur 40:6-8, Ibrani 10:1-14, dan Wahyu 5:9-14. Pondasi untuk memahami pendamaian diletakkan dalam sistem korban yang menampilkan pendamaian sebagai kegiatan khusus yang berkorban dari imamat untuk membawa rekonsiliasi bagi dosa. Mazmur 40 mengembangkan gagasan ini secara eksplisit dengan menyatakan perlunya ketaatan dan menggambarkan tipe raja yang taat. Ibrani 10 menunjukkan bagaimana Imamat 16 dan Mazmur 40 menunjuk kepada Kristus-imam-raja yang adalah korban yang sempurna, efektif, dan sekali untuk selamanya. Terakhir, bicara tentang penundukan semua orang pada pemerintahan Kristus (Ibr. 10:12-13), mengarah ke Wahyu 5 di mana orang-orang yang telah didamaikan memiliki akses ke hadirat Kristus yang memerintah.